The effectiveness of using furnishings to improve the housing acoustic of low-cost flats in Malaysia - Liew, Yee Hua; Nazli Che Din (Penerbit Universiti Kebangsaan Malaysia, 2020)
The acoustical performance of high-rise residential housing in the marketplace of Malaysia is under satisfactory as the residents are consistently dealing with internal and external noises. One of the most practical solutions to improve housing indoor acoustic comfort is by introducing furniture and furnishings which can absorb sound energy. The objective of this research is to evaluate and compare the acoustical performance of public low-cost multi-storey housing (PPR low-cost flats) in Kuala Lumpur in unfurnished and furnished conditions. Three scenarios: (1) empty housing unit without any furnishing, (2) housing unit furnished with basic furniture, (3) housing unit furnished with basic furniture and extra furnishings (carpet and curtains), were modelled in Google SketchUp and exported into ODEON Room Acoustic Software 13.0 for simulation. Results were then compared in the parameter of Reverberation Time (RT) and Speech Transmission Index (STI). Based on results, scenario (3) demonstrated the best improved result in overall after evaluating the performance of acoustical criteria. The more the furniture and furnishings with higher absorption coefficient introduced in the housing unit, the lesser the RT and higher STI, resulting in a better indoor acoustical environment.